7.2 Relative sea-level changes at Clachan harbour, Raasay, Scottish Hebrides (Scottish Archaeological Internet Reports, 2009)
An intertidal organic deposit enclosed within estuarine clastic sediments, is described for Clachan harbour, Raasay, the Inner Sound. The organic sediments are over and underlain by fine sands and silts containing marine microfossils. Macrofossil analyses (pollen and diatoms) indicate a regression and subsequent transgression at the site during the early Holocene. The altitude at which early Holocene marine regression and transgression is recorded is less than at sites located on the Scottish mainland at Arisaig. This reflects the geographical position of Raasay, located on the periphery of the glacio-isostatic uplift centre, under the influence of differential isostatic uplift across the Inner Hebrides.